Analisis Manajemen Laba Dan Kinerja Keuangan Perusahaan Pengkuisisi Sebelum Dan Sesudah Merger Dan Akuisisi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2015 - Endah Setya Rahayu; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRAK The purpose of this study is to determine whether there is a earning management action on the acquirer before and after the company did mergers and acquisitions as well as to determine whether there are differences in financial performance of the acquirer merger and acquisitions. Earnings management is measured by proxy Discretionary Accruals (DA). Financial performance measured by financial ratios, that is NPM (Net Profit Margin), ROA (Return OnAsset), and TATO (Total Asset Turnover). The population in this study are all companies listed on the Indonesian stock exchange (BEI) in 2014-2015. The samples was taken based on purposive sampling with total sample of 20 companies. The method of analysis in the study using paired sample T-test. Based on the result of this study in the know that the acquirer company proven to perform actions practice earnings management with profit decreasing action pattern (income decreasing). And Discretionary Accruals (DA) there are significant differences. Furthermore, the company’s financial performance as measured by the ratio NPM (Net Profit Margin), ROA (Return On Asset), and TATO (Total Asset Turnover) there is no significant difference in the acquirer’s financial performance before and after merger and acquisition.Keyword: Mergers, Acquisitions, Earnings Management, Financial Performance